Dezocine Prevents Postoperative Hyperalgesia in Patients Undergoing Open Abdominal Surgery. (11th June 2015) - Yu, Fang; Zhou, Jie; Xia, Suyun; Xu, Huan; Wang, Xiangrui
Abstract : Objective . Postoperative hyperalgesia is very frequent and hard to treat. Dezocine is widely used and has a modulatory effect for thermal hyperalgesia in animal models. So, this study was designed to investigate the potential role of dezocine in decreasing postoperative hyperalgesia for patients undergoing open abdominal surgery. Methods . This is a randomized, double-blinded, and placebo-controlled trial. 50 patients for elective open gastrectomy were randomly allocated to either a true treatment group (0.15 mg/kg intravenous dezocine at the end of surgery) or a sham treatment group (equivalent volume of saline) in a 1 : 1 ratio. Patients were followed up for 48 hours postoperatively and pain threshold to Von Frey filaments, pain scores, PCIA consumption, rescue analgesics use, sedation score, and occurrence of postoperative nausea and vomiting were recorded. Results . Patients in the true treatment group experienced statistically significantly higher pain threshold on forearm and smaller extent of peri-incisional hyperalgesia than the sham treatment group. Rescue analgesic use, cumulative PCIA consumption, and pain scores were statistically significantly decreased in the true treatment group compared to the sham treatment group. Conclusions . Dezocine offers a significant antihyperalgesic and analgesic effect in patients undergoing elective open gastrectomy for up to 48 hours postoperatively.